2015
DOI: 10.1037/a0038757
|View full text |Cite
|
Sign up to set email alerts
|

Social resource correlates of levels and time-to-death-related changes in late-life affect.

Abstract: Little is known regarding how well psychosocial resources that promote well-being continue to correlate with affect into very late life. We examined social resource correlates of levels and time-to-death related changes in affect balance (an index of affective positivity) over 19 years among 1,297 by now deceased participants (aged 69 to 103 at first assessment, M = 80 years; 36% women) from the Australian Longitudinal Study of Aging. A steeper decline in affect balance was evident over a time-to-death metric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 78 publications
(111 reference statements)
6
28
0
Order By: Relevance
“…Converging with prior evidence, we found that people who died at younger ages, were less socially active, and suffered from disability or a compromised ability to carry out Instrumental Activities of Daily Living reported lower levels of well-being close to death (see Brandmaier et al, 2017;Windsor et al, 2014). Moving beyond previous reports and demonstrating the power of personality to predict important life outcomes across the entire life span, our results further revealed that personality traits predict late-life well-being above and beyond these well-established predictors.…”
Section: Discussionsupporting
confidence: 72%
“…Converging with prior evidence, we found that people who died at younger ages, were less socially active, and suffered from disability or a compromised ability to carry out Instrumental Activities of Daily Living reported lower levels of well-being close to death (see Brandmaier et al, 2017;Windsor et al, 2014). Moving beyond previous reports and demonstrating the power of personality to predict important life outcomes across the entire life span, our results further revealed that personality traits predict late-life well-being above and beyond these well-established predictors.…”
Section: Discussionsupporting
confidence: 72%
“…This suggested that older people might do better in avoiding negative affective arousal in their everyday life (note, however, that age-related decline of NA was not consistently confirmed in all studies [24,32]). In contrast, recent evidence on terminal decline in affective well-being points to the limits of self-regulatory processes in the late phase of life [17,36,48,50]. Altogether, changes of affective well-being in old age lead to the question whether affective reactivity to daily stressors changes in a systematic age-related way across the adult life span.…”
Section: Schlüsselwörtermentioning
confidence: 70%
“…Though not independent of one another, the convergence of findings across approaches adds to the credibility of our results about the importance of social resources for late-life well-being. We also consider it important to keep the single-phase model because it helps connecting the current study to the large majority of earlier reports on late-life well-being that were based on relatively few data points and thus did not allow apply multi-phase models (Berg, Hassing, Thorvadsson, & Johansson, 2011; Carmel, Shrira, & Shmotkin, 2013; Diehr, Williamson, Burke, & Psaty, 2002; Mroczek & Spiro, 2005; Palgi, Shrira, Ben-Ezra, Spalter, Shmotkin, & Kavé, 2010; Palgi, Shrira, Ben-Ezra, Spalter, Kavé, & Shmotkin, 2014; Schilling et al, 2013; Vogel, Schilling, Wahl, Beekman, & Penninx, 2012; Windsor, Gerstorf, & Luszcz, 2015). …”
Section: Discussionmentioning
confidence: 99%